Evaluation for Error in Translation: A Study of Academic Translations of Prospective Undergraduate Students - Nasution, Dewi Kesuma; Niswa, Khairun (Universitas Islam Negeri Palopo, 2025)
This study scrutinizes the quality of translation for students who use translation assistance. A new text translated by students is then studied to see how successful students are at translating the text. First, the quality of the translation was analyzed using a scoring rubric in the form of the first, which deals with the perception of the source text message related to the accuracy of the translation, including the translation which has an inaccurate effect on understanding the source text and classified into eight categories: faux sens, nonsense, additions, omissions, unresolved extralinguistic references, loss of meaning, inappropriate linguistic variations (registers, styles, dialects). Second, nonconforming renderings that affect target language (TL) expressions are divided into five categories: spelling, grammar, lexical items, text, and style. Finally, preliminary presentation affects the delivery of the source text's primary or secondary function. The research uses content analysis design and descriptive qualitative methods as the umbrella. The study's results found that there were few grammatical omissions because the target language had absorption from the source language. In table 1, the translator does not make mistakes regarding style and text because, in principle, the language in the news is the standard language. Linguistic problems include grammatical differences, lexical ambiguity, and meaning ambiguity. At the same time, cultural issues refer to different situational features. This classification coincides with, for example, regional languages such as Sundanese, Malay, or Arabic